Response to eculizumab in patients with myasthenia gravis recently treated with chronic IVIg: a subgroup analysis of REGAIN and its open-label extension study. (April 2020) - Jacob, Saiju; Murai, Hiroyuki; Utsugisawa, Kimiaki; Nowak, Richard J.; Wiendl, Heinz; Fujita, Kenji P.; O'Brien, Fanny; Howard, James F.
Background: In the phase III eculizumab for refractory generalized myasthenia gravis REGAIN study [ClinicalTrials.gov identifier: NCT01997229] and its open-label extension (OLE) [ClinicalTrials.gov identifier: NCT02301624], patients with treatment-refractory antiacetylcholine receptor antibody-positive generalized myasthenia gravis had clinically meaningful improvements with eculizumab versus placebo. This subgroup analysis evaluated data from patients with a recent history of chronic intravenous immunoglobulin (IVIg) use before study entry. Methods: The subgroup comprised patients who had received IVIg at least four times in 1 year, with at least one IVIg treatment cycle during the 6 months before the first REGAIN study dose. Data from REGAIN and the OLE were analyzed. Response to eculizumab versus placebo was assessed using four validated, disease-specific measures. Incidences of exacerbations and safety endpoints were recorded. Results: The subgroup had similar patient and disease characteristics as the overall REGAIN population. Clinical assessments showed sustained eculizumab efficacy during REGAIN and the OLE over 18 months. Patients receiving placebo in REGAIN experienced rapid improvements in assessment scores when treated with eculizumab in the OLE. There was a lower rate of disease exacerbations with eculizumab than with placebo during REGAIN, and eculizumab was well tolerated. Conclusion: Eculizumab treatment, compared with placebo, results in meaningful clinical improvements and fewer disease exacerbations for patients who previously received chronic IVIg. Trial registration: REGAIN [ClinicalTrials.gov identifier: NCT01997229]; REGAIN open-label extension [ClinicalTrials.gov identifier: NCT02301624].